Botox nation : changing the face of America - Berkowitz, Dana (New York university Press, 2017)
The first in-depth social investigation into the development and rising popularity of Botox The American Society for Aesthetic Plastic Surgery estimates there are about two-and-a-half million Botox procedures performed annually, and that number continues to increase. The procedure is used as a preventive measure against aging and a means by which bodies, particularly women’s, can be transformed and “improved” through the appearance of youth. But why is Botox so popular, and why is aging such a terrifying concept? Botox Nation draws from engaging, in-depth interviews with Botox users and providers as well as Dana Berkowitz’s own experiences receiving the injections. The interviews reveal the personal motivations for using Botox and help unpack how anti-aging practices are conceived by, and resonate with, everyday people. Berkowitz is particularly interested in how Botox is now being targeted to younger women; since Botox is a procedure that must be continually administered to work, the strategic choice to market to younger women, Berkowitz argues, aims to create lifetime consumers. Berkowitz also analyzes magazine articles, advertisements, and even medical documents to consider how narratives of aging are depicted. She employs a critical feminist lens to consider the construction of feminine bodies and selves, and explores the impact of cosmetic medical interventions aimed at maintaining the desired appearance of youth, the culture of preventative medicine, the application of medical procedures to seemingly healthy bodies, and the growth and technological advancement to the anti-aging industry. A captivating and critical story, Botox Nation examines how norms about bodies, gender, and aging are constructed and reproduced on both cultural and individual levels.